Expressive Speech Actions in Column YouTube Account Comments kompas.com Cyber Pragmatics Perspective - Fiamanillah; Fatmawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The purpose of this study is to explore and elaborate the functions of expressive speech acts based on cti